2019
DOI: 10.22575/interventionalradiology.2018-0019
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoaneurysm Formation and Hemobilia as Late Complications after Transarterial Chemoembolization and Radiofrequency Ablation for Hepatocellular Carcinoma

Abstract: An 82-year-old man underwent transarterial chemoembolization and radiofrequency ablation (RFA) for a 42-mm hepatocellular carcinoma in segment IV. Thirty-eight months later, he was admitted to our hospital for acute cholecystitis that had spread to the ablated area. After he started antibiotic treatment, the inflammatory reaction gradually improved, but he developed acute cholangitis, and massive hemobilia was observed during endoscopic retrograde biliary drainage. An angiogram showed both a pseudoaneurysm of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Takaki et al have shown that arterial embolization was a significant independent factor for reducing the risk of major hemorrhage during RFA for liver tumors (p < 0.01; odds ratio, 4.3; 95% CI, 1.5-12.7) [20]. However, a recent case report revealed formation of a pseudoaneurysm of the hepatic artery near the ablated area, due to a late complication of infection three years post-TACE and RFA for HCC [50]. Therefore, the risk of hemorrhagic complications should be considered, even several years after RFA, especially when the ablated area is located near the hepatic artery.…”
Section: Transarterial Embolizationmentioning
confidence: 99%
“…Takaki et al have shown that arterial embolization was a significant independent factor for reducing the risk of major hemorrhage during RFA for liver tumors (p < 0.01; odds ratio, 4.3; 95% CI, 1.5-12.7) [20]. However, a recent case report revealed formation of a pseudoaneurysm of the hepatic artery near the ablated area, due to a late complication of infection three years post-TACE and RFA for HCC [50]. Therefore, the risk of hemorrhagic complications should be considered, even several years after RFA, especially when the ablated area is located near the hepatic artery.…”
Section: Transarterial Embolizationmentioning
confidence: 99%